Urolithiasis in a female miniature potbellied pig. Issue 3 (15th July 2019) - Needleman, Abigail; Videla, Ricardo
Abstract : A five‐year‐old female spayed Vietnamese potbellied pig was evaluated due to a chronic history of dysuria and pollakiuria as well as lack of faecal output for one week. Physical examination revealed vitals within normal parameters and to facilitate further workup evaluation, the patient was anaesthetized. Complete blood count and chemistry panel values were unremarkable. Ultrasonography of the bladder indicated the presence of uroliths, and this was confirmed with abdominal radiographs. A cystotomy was performed to remove the uroliths, and an enaema was administered to relieve the constipation. The patient recovered from anaesthesia uneventfully and was discharged after four days of hospitalisation. Analysis revealed that the stones were composed of calcium phosphate carbonate; husbandry and medical management changes were implemented to prevent reoccurrence. Urolithiasis is an uncommon finding in female pigs; this case report describes a comprehensive clinical workup and treatment of a female adult pig with urolithiasis.